Nigerian Yearbook of International Law 2017 (Nigerian Yearbook of International Law ,, 2018)
This book is the inaugural edition of the Nigerian Yearbook of International Law. The Yearbook is a necessary and timely publication that provides a forum for critical discourse on developments in international law, particularly where this has relevance for Nigeria, Africa and its people including those in the diaspora. The articles in this first volume explores topics under the following themes: International Law and Regional Systems, Contemporary Challenges/Emerging Issues, Criminal Law and Natural Resources/Environmental Law. There is also a section, which provides a comprehensive review of key decisions in African and International Courts/Tribunals. Contributors to this edition are international law jurists from across the world, including eminent judges of international tribunals, leading academics and an international diplomat. .